Leitura e escrita recombinativa com pessoas com desenvolvimento atípico: caracterização e análise das publicações nacionais - Souza, Monique Luzia de (2020)
Studies in Brazil have shown that students with atypical development often perform unsatisfactorily in academic assessments, including reading and writing. In order to make reading and writing teaching programs more economical and effective, recombinative generalization has been investigated, once it allows the expansion of reading and writing to text units that were not directly taught. However, the restricted stimulus control (RSC) mainly observed in the atypical development population can hinder such expansion. Because of that, in Study 1, an update on the topic was done, aiming to describe Brazilian researches that assessed the emergence of recombinative reading/writing. Theses and dissertations from 2011 to 2019, and articles published until 2019 were collected from digital information sources, with 133 selected works. It was identified that UFSCar, PUC-SP and UFPA were the Brazilian universities with the highest production of theses and dissertations, and, in addition to UnB, had the main advisors on the subject. From 2009 to 2016, more than a half of the articles were published, and UFSCar, UnB, INCT-ECCE, UEL and UFSC were the Brazilian institutions with the largest number of articles. Participants were usually children with typical development enrolled in elementary school. Study 2 was done with the aim of analyzing the characteristics of the Brazilian researches that were carried out with the atypical development population, and the aim of identifying relevant variables for the emergence of recombinative reading/writing in this population. The studies from Study 1 and those from a previous literature review were analyzed; 45 studies were selected in the first phase (analysis of basic data) and 29 were selected in the second phase (full analysis). The results show that: (a) the first Brazilian work with the atypical development population was published in 1994; (b) from 2006 onwards, there was stable production of theses and dissertations; (c) UFSCar, UFPA and PUC-SP were the universities with the highest production of theses and dissertations, with emphasis on UFSCar; (d) UFPA, UFSCar and INCT-ECCE were the institutions with the largest number of published articles; (e) several diagnoses have been identified, with emphasis on autism spectrum disorder (ASD); (f) the training sessions were usually individual and applied by the researchers; (g) procedures that promote discrimination of smaller units have proven to be more effective; and (h) few studies have evaluated the maintenance of results. It is recommended that future studies investigate teaching procedures little applied to such population, use complex textual units, and perform group training, with the teachers as intervention agents, aiming at the training of such professionals